Between Christ and Caliph : law, marriage, and Christian community in early Islam - Weitz, Lev E. (Divinations., 2018)
In Between Christ and Caliph, Lev E. Weitz examines the multiconfessional society of early Islam through the lens of shifting marital practices of Syriac Christian communities, arguing that interreligious negotiations lie at the heart of the history of the medieval Islamic empire.